Molecular Characterization and Seasonal Variation in Primary and Secondary Organic Aerosols in Beijing, China. Issue 21 (6th November 2018) - Li, Linjie; Ren, Lujie; Ren, Hong; Yue, Siyao; Xie, Qiaorong; Zhao, Wanyu; Kang, Mingjie; Li, Jie; Wang, Zifa; Sun, Yele; Fu, Pingqing
Abstract: Biomass burning (BB) aerosols, primary biological aerosol particles, and secondary organic aerosols, are critical components of particulate matter in the atmosphere. In this study, saccharides, lignin/resin acids, biogenic secondary organic aerosols tracers, aromatic acids, and hydroxyacids/polyacids were measured in total suspended particles collected from April 2012 to March 2013 at an urban site in Beijing using gas chromatography/mass spectrometry. The concentration of levoglucosan was elevated during 18–20 June. The high ratio of levoglucosan to mannosan and low ratio of galactosan to mannosan in June demonstrated the influence of wheat straw combustion in the North China Plain via long‐rang transport. Sucrose, glucose, and fructose were more abundant in April, the spring bloom season. The maximum trehalose content (298 ng/m 3 ) occurred during a dust storm (27–29 April) with the highest stable carbon isotope ratio ( δ 13 C, −21.2‰) of total carbon. Fungal spore tracers (arabitol and mannitol) peaked in summer. The largest concentrations of the oxidization products of isoprene and α/β‐pinene also occurred in summer. However, the β‐caryophyllene tracer was much more abundant on long‐lasting haze days in winter and was positively related to levoglucosan. The contributions of biogenic primary sources (plant debris, fungal spores, and BB) to organic carbon were estimated to be in range of 2.64–35.2% (11.8%), with BB being the predominant source. Biogenic secondary sources (isoprene, α‐pinene, and β‐caryophyllene) and anthropogenic secondary source (naphthalene) accounted for 0.23–10.9% (3.36%) of organic carbon with large contributions in summer and winter, respectively. Key Points: Biomass burning was the dominant contributor during the year, especially in the harvest and domestic heating seasons The maximum trehalose content occurred during a dust storm (27–29 April 2012) in Beijing Isoprene and α/β‐pinene SOA tracers peaked in summer, while the β‐caryophyllene SOA tracer increased in winter due to biomass burning